Analisis Manajemen Rantai Pasokan Produk Pertanian Pasca Panen - Muhamad Arief Noor; Siti Mulasih; Sukardi Sukardi; Tohiroh Tohiroh (Jurnal Ilmiah Ekonomi, Manajemen dan Bisnis, 2024)
This study aims to analyze the supply chain management of post-harvest agricultural products with a focus on increasing efficiency and reducing post-harvest losses. The research subjects are farmers in Cipayung Mas Ciputat, South Tangerang, Banten, Indonesia. This research was conducted in May 2024. The research method used is a qualitative descriptive method with a case study approach. Data were collected through in-depth interviews, field observations, and document analysis. Research participants include farmers, collectors, traders, and distributors. Data processing was carried out using thematic analysis to identify patterns in supply chain management and factors affecting post-harvest losses. The results of the study show that effective supply chain management can significantly reduce post-harvest losses and increase farmers' profits. Key factors identified include efficient storage, rapid distribution, and the use of modern technology in post-harvest processing. The study also found that training and education for farmers on good storage and distribution techniques are essential to improve the quality and quantity of produce reaching the market. This research provides recommendations for stakeholders to invest in storage infrastructure and processing technology, as well as to conduct regular training programs for farmers. By implementing better supply chain management, it is expected to improve farmers' welfare and regional food security